An Analysis of Archetype of Main Character Jim White in Mcfarland USA movie - Raka Adam Pangestu; Defi Julianti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The topic of this research is to analyze about archetype. Archetype is representation of metaphysical appeared from collective unconscious that can strengthen the personality of a person. This research’s objective is analyzing the archetype of main character Jim White that can show the personality of the person itself based on archetype perspective and alsofind ego that appear in the main character. The theory that the researcher used is archetype theory that develop by Jung. This research uses descriptive qualitative research that used script dialogue of the movie as the data to find the result. The researcher found 22 data related to ego (4 data) and seven archetype that appeared, those are persona (5 data), shadow (2 data) , anima (1 datum), hero (1 datum), great mother (2 data), wise old man ( 2 data) and self (5 data).